Response Surface Methodology Approach to Optimize the Expression of Thioredoxin-MOG Fusion Protein - Maryam Radmard; Atieh Hashemi (Tabriz University of Medical Sciences, 2024)
Background: The N-terminal domain of the myelin oligodendrocyte glycoprotein (MOG) has been shown to generate experimental autoimmune encephalomyelitis (EAE), an animal model of MS. A considerable amount of MOG must be accessible for EAE induction. Here, for the first time, Response Surface Methodology-Box-Behnken (RSM-BBD) was employed to identify the ideal culture conditions for causing Escherichia coli (E. coli) BL21 to overproduce the Thioredoxin-MOG (Trx-MOG) fusion protein. The RSM method is a powerful, efficient, and reliable alternative to the One-Factor-At-A-Time (OFAT) method in optimizing process variables, allowing for a smaller number of experimental runs, investigating variable interaction, and being cheaper and less time-consuming. Methods: Here, using the 29 experimental assays, the direct and indirect effects of factors including post-induction time, IPTGinducer concentration, pre-induction optical density, and post-induction temperature on the protein expression level content were evaluated. Results: The proposed quadratic model demonstrated a significant effect of the two variables A (time) and C (temperature) on protein synthesis. An inducer concentration of 0.491 mM, the pre-induction optical density (OD600) of 0.8, and a temperature of 23 °C for 23.878 hours were found to be the best growth conditions for high yield Trx-MOG synthesis. The optimum protein concentration was attained (163.96 µg/mL) and was within the range of (200.04 µg/mL), which was the value predicted. Conclusion: The study concluded that RSM optimization effectively increased the production of Trx-MOG in E. coli, which could have the potential for large-scale fermentation.